Dynamics Of Total Suspended Solid (TSS) Around Coral Reef Beach Damas, Trenggalek - Mayshita Yonar; Oktiyas Muzaky Luthfi; Andik Isdianto (Universitas Airlangga, 2021)
Total suspended solids (TSS) are sediment material that floats in the water column that moves without touching the water bed, influenced by input from land, river flow, and water oceanography factors. TSS is closely related to sedimentation, which can harm aquatic ecosystems, especially coral reefs. This research was conducted using TSS data as well as flow data for each season (May, June, October 2019, February and March 2020) to know the distribution of suspended solids concentration, knowing the dynamics of changes in TSS concentrations on Damas Beach by season, and to determine the relationship TSS with the growth of coral reefs at Damas Beach. TSS levels in Damas waters are quite high, which can be indicated by the turbid waters. TSS levels in March 2020 showed dominating results with a range of 37.8–72.6 mg/L and an increase in the range of 72.7-145 mg/L. The highest distribution of TSS on Damas Beach is found in the Rainy season.